THE IMPACT OF BLENDED LEARNING ON STUDENTS’ WRITING ABILITY: SYSTEMATIC REVIEW - Vonny; Muhammad Sahrir Aras (CV. ADIBA AISHA AMIRA, 2026)
Blended learning has become an increasingly popular instructional approach in language education, particularly in improving students’ writing ability. This study aims to examine the impact of blended learning on students’ writing skills through a systematic review of relevant scholarly literature. The data were collected from reputable academic databases and analyzed using a systematic review procedure involving article identification, screening, eligibility assessment, and synthesis of findings. The review indicates that blended learning positively influences students’ writing ability by providing flexible learning environments, increasing opportunities for practice, and facilitating timely feedback through digital platforms. In addition, the integration of online and face-to-face instruction encourages student engagement, collaboration, and autonomous learning. However, several challenges were also identified, including technological limitations, unequal digital literacy among students, and the need for effective instructional design. Overall, the findings suggest that blended learning is an effective approach for enhancing students’ writing ability when supported by adequate technological infrastructure and appropriate pedagogical strategies. This study highlights the importance of integrating digital learning environments with traditional classroom instruction to improve writing outcomes in language education.